2010
DOI: 10.1021/nl1007085
|View full text |Cite
|
Sign up to set email alerts
|

LiMnPO4 Nanoplate Grown via Solid-State Reaction in Molten Hydrocarbon for Li-Ion Battery Cathode

Abstract: Electrochemically active LiMnPO(4) nanoplates have been synthesized via a novel, single-step, solid-state reaction in molten hydrocarbon. The olivine-structured LiMnPO(4) nanoplates with a thickness of approximately 50 nm appear porous and were formed as nanocrystals were assembled and grew into nanorods along the [010] direction in the (100) plane. After carbon coating, the prepared LiMnPO(4) cathode demonstrated a flat potential at 4.1 V versus Li with a specific capacity reaching as high as 168 mAh/g under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
262
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(283 citation statements)
references
References 46 publications
(171 reference statements)
13
262
2
2
Order By: Relevance
“…In more recent reports, carbon-coated nanostructures have enabled stable cycling as a result of diminishing Li + diffusion paths, accommodation of the volume induced change on cycling (~9.5%) [459], and enhanced electrical conductivity. Choi and co-workers [458], have demonstrated enhanced performance of carbon-coated LiMnPO4 nanoplates, with stable cycling and high gravimetric capacity. The LiMnPO4 nanoplates, which were in the order of 50 nm thick, were prepared by a surfactant (oleic acid)-assisted solid-state reaction of MnCO3 and NH4H2PO4, with molten paraffin serving as co-solvent.…”
Section: Other Transition Metal Phosphates (Limpo4)mentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent reports, carbon-coated nanostructures have enabled stable cycling as a result of diminishing Li + diffusion paths, accommodation of the volume induced change on cycling (~9.5%) [459], and enhanced electrical conductivity. Choi and co-workers [458], have demonstrated enhanced performance of carbon-coated LiMnPO4 nanoplates, with stable cycling and high gravimetric capacity. The LiMnPO4 nanoplates, which were in the order of 50 nm thick, were prepared by a surfactant (oleic acid)-assisted solid-state reaction of MnCO3 and NH4H2PO4, with molten paraffin serving as co-solvent.…”
Section: Other Transition Metal Phosphates (Limpo4)mentioning
confidence: 99%
“…One such example is LiMnPO4 [447][448][449][450][451][452][453][454][455][456][457][458], which is isostructural to that of olivine LiFePO4, while possessing a higher operating voltage (4.1 vs. 3.5 V, respectively) [378,448], and hence energy densities which could exceed 700 Wh kg -1 . At this point, it should be suggested that LiMnPO4 represents a more realistic candidate compared to LiCoPO4 or LiNiPO4, since the working voltage of LiCoPO4 or LiNiPO4 electrodes (4.9 and 5.1 V, respectively), currently lies outside regions of stability of the commonly-employed organic (carbonate) electrolytes [378].…”
Section: Other Transition Metal Phosphates (Limpo4)mentioning
confidence: 99%
“…When the same synthesis method is applied to generate both, the particle size of LiFePO 4 is smaller than the one of LiMnPO 4 [25]. Various synthesis routes have so far produced morphologies of LiMnPO 4 with spherical [26], plate-shaped [4,27,28], rods [25,29,30], wires [31,32], microporous [33] and flower-like structures [34,35]. Their electrochemical properties were affected by different morphologies of LiMnPO 4 [36], which may have different orientations of Li þ diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The rate capabilities of LiMnPO 4 /C and LiCoPO 4 /C are significantly poorer compared with the LiFePO 4 , which may be explained by the difference in intrinsic material properties, such as the miscibility gap. The electrochemical properties of the LiMnPO 4 /C core−shell nanocomposite is better than LiMnPO 4 /C particles (30 nm), 42 nanometric LiMnPO 4 , 43 LiMnPO 4 nanoplate, 44 and carboncoated LiMnPO 4 . 45 The improved electrochemical performance may be attributed to small LiMnPO 4 core coated with a uniform carbon shell.…”
mentioning
confidence: 95%